Are Canadian Regional Business Cycles All Alike? - Rodriguez, Gabriel (Université d'Ottawa | University of Ottawa, 2003)
Using three different econometric methodologies, this paper identifies business cycles fluctuations in Canadian regions using quarterly real GDP for the period 1961:1 - 2000:1. With the estimates of the transitory and permanent components, as well as filtered and smoothed probabilities of being in times of recession, a chronology for the regional business cycles fluctuations is presented. For the purpose of comparison, results for Canada and the US are also included. Lastly, evidence about correlations between different business cycles is also presented. / Utilisant trois différentes méthodologies économétriques, ce travail identifie les fluctuations dans les cycles économiques des régions canadiennes utilisant les données trimestrielles sur le PIB réel pour la période de 1961:1 à 2000:1. Avec les estimés des composantes transitoires et permanentes, ainsi qu’à l’aide des probabilités d’être en période de récession, un ordre chronologique pour les fluctuations des cycles économiques régionaux est établi. Pour des fins de comparaison, les résultats pour le Canada, ainsi que pour les États-Unis sont présentés. Dernièrement, l’évidence de corrélation entre les différents cycles économiques est aussi présentée.
Keywords: Regional Business Fluctuations; Markov Switching; Unobserved Components; Fluctuations économiques régionales; changements de régime de Markov; composantes inobservées